(untitled) (Damascus University Journal of agriculture sciences, 2023)
This study aimed to evaluate pregnancy rates in Awassi ewes, after substitution of hMG for eCG with progestagens during the non-breeding season. 20 multiparous Awassi ewes were randomly allocated into two equal treatment groups. Vaginal sponges have been inserted for 14 days to all of treatment groups. along with intravaginal sponges withdrawal, Follicular development was induced in the control group with 750 IU eCG and in the second group with 25 IU hMG and ovulation was induced 52h after hMG administration with 1000 IU hCG. All ewes were artificially inseminated at fixed time after 24h of hCG administration with fresh diluted semen collected using an electroejaculator just before insemination time. An ultrasound scanner equipped with a linear transducer probe with a frequency of 7.5 MHz was used to monitor ovarian follicles for three consecutive days, starting at gonadotropin administration, and to diagnose pregnancy at 35 d post A.I. Statistical differences (P<0.05) were reported in the number of small, medium, and large follicles after 48 h of gonadotropin injection, as the hMG group outperformed (P<0.01) in the number of large follicles the eCG (8.00 vs. 2.38, respectively). No statistical differences (P>0.05) were reported in pregnancy rate after treatment with hMG compared to eCG, However, the hMG group outperformed the eCG group in the pregnancy rate by 20%. As for the mean estradiol concentrations, the eCG treated ewes recorded a linear increase, while the estradiol levels in the hMG group began to decline 24 hours after the hMG injection and continued to decline linearly until the end of the blood sampling program. From these results, it may be concluded that hMG-based protocols with progestagens are promising alternatives for traditional eCG-based protocols to induce follicular development/ estrus outside of the breeding season in Awassi ewes. Key words: hMG– eCG - intravaginal sponges - Awassi ewes.